Pseudonmization Techniques for Clinical Data: Privacy Study in Sultan Ismail Hospital Johor Bahru - Abd.Rahim, Y; Sahib, S; Abd Ghani, M. K. (2011)
Privacy includes the right of individuals and organizations to determine for themselves when, how and to what extent information about them is communicated to others. The growing need of managing large amounts of data in hospital or clinical raises important legal and ethical challenges. This paper introduces and show the testing implementation of the privacy-protection problems, and highlights the relevance of trusted third parties and of privacy-enhancing techniques (PETs) in the context of data collection, e.g., for research. Practical approache on the pseudonymization model for batch data collection are presented. The actual application of the described techniques today proves the possible benefits for medicine that innovative privacy-enhancing techniques can provide. Technical PET solutions can unlock valuable data sources, otherwise not available.